2021
DOI: 10.3390/ma14030666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corroded Surface Morphology on Ultra-Low Cycle Fatigue of Steel Bridge Piers

Abstract: Corrosion is a common form of durability degradation of steel bridges. Corrosion morphology affects stress distribution under cyclic loads and causes strain concentrations in pits, thus affecting the mechanical properties of steel structures, including ultra-low cycle fatigue (ULCF). To precisely simulate corrosion morphology and investigate the ULCF failure mechanism of corroded steel piers, a sculpting method was applied to mesh units using three-dimensional surface morphology data of corroded steel specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…At a higher displacement amplitude of 5 mm, the fatigue life decreased by about 45% from 33.5 to 18.5 cycles with an increase in surface roughness from 20 to 100 μm. Song et al, (2021a) observed a similar reduction effect in the ULCF life of steel bridge piers with the increase in corrosion level. In another study by Song et al, (2021b), it was investigated that corrosion induced surface roughness has a dominant impact on the ULCF life of steel specimens.…”
Section: Effect Of Constant Loading Amplitude Under Variable Surface ...supporting
confidence: 58%
See 1 more Smart Citation
“…At a higher displacement amplitude of 5 mm, the fatigue life decreased by about 45% from 33.5 to 18.5 cycles with an increase in surface roughness from 20 to 100 μm. Song et al, (2021a) observed a similar reduction effect in the ULCF life of steel bridge piers with the increase in corrosion level. In another study by Song et al, (2021b), it was investigated that corrosion induced surface roughness has a dominant impact on the ULCF life of steel specimens.…”
Section: Effect Of Constant Loading Amplitude Under Variable Surface ...supporting
confidence: 58%
“…McKelvey and Fatemi (2012) checked the fatigue life of forged steel and developed life curves as a function of hardness based on their experimental findings. Song et al, (2021aSong et al, ( , 2021b) investigated the ULCF properties and fracture process of corroded steel and found that fatigue life is significantly reduced by the increasing level of surface roughness induced by the corrosion process. Additionally, processing parameters are known to have a strong impact on fatigue life, and variation in surface morphology largely affects the LCF life (Hasunuma et al, 2019).…”
Section: Nomenclaturementioning
confidence: 99%
“…When the corrosion rate γ ≤ 10%, the number of pits increases with the corrosion rate, and the distribution of the pits became denser which caused the pits larger and deeper. When the corrosion rate is 15% ≤ γ ≤ 25%, the corrosion pits became clear and denser, and the corrosion pits are assumed as hemispherical [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Equation (23) illustrates the loss of dissipation energy due to electrochemical corrosion. It can be clearly seen in Figure 9 and Figure 10 that the corrosion pit distributes on the surface of the whole specimen, and the shape of the corrosion pit is presented as a hemisphere or semi-ellipsoid [ 35 , 39 ]. It assumes that the density of steel keeps constant.…”
Section: Equivalent Reduction Thickness and Verificationmentioning
confidence: 99%
See 1 more Smart Citation